SMS Gateway Based Academic Information System as a Communication Media to support School Performance - Eni Endaryati; Vivi Kumalasari Subroto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The development of the world accompanied by rapid technological developments requires every individual or institution to continue to follow the development of information technology so that they can provide satisfactory service which is the main goal that must be achieved by every government and private institution, which includes the world of education, namely schools, especially the delivery of information. One of the delivery of information is by SMS. The old system of delivering information, among others, is by attaching grades to each class or for job vacancy information through job vacancies information boards so that the delivery of information is felt to be less fast and also if the school area is very large and the means of communication are inadequate. With this SMS-based information system, it can be a solution to solve existing problems in addition to cheap and fast SMS technology, as well as with a website system display that can be accessed by all parties who use it, an effective and efficient job will be achieved in supporting activities on the internet. schools to become educational and training institutions for producing professional and independent workers can be achieved.